Postmodern - "Malpas, Simon" (London, 2007)
Postmodern Literature offers a comprehensive survey of the field, from its emergence in the mid-twentieth century to the present day. It offers an unparalleled examination of all facets of postmodern writing that helps readers to understand how fiction and poetry, literary criticism, feminist theory, mass media, and the visual and fine arts have characterized the historical development of postmodernism.
Keywords: Postmodernism